ASPECTOS HISTÓRICOS DO ENSINO SECUNDÁRIO DA MATEMÁTICA EM CAMPO GRANDE NO SUL DE MATO GROSSO NA PRIMEIRA METADE DO SÉCULO XX. - Julio Veloso dos Santos (2022)
This master's thesis has as main research objective to describe and analyze historical aspects of secondary mathematics teaching in Campo Grande, Mato Grosso do Sul, in the first decades of the 20th century. The sources used included digitized records in the Digital Hemeroteca of the National Library, regional historical books, documents obtained from document collections in the region, as well as bibliographical indications. The general organization of the work and the carrying out of the analyzes were conceived based on concepts proposed by cultural historian Peter Burke and by other authors who follow the same orientation. Part of a critical methodological approach, structured in the heptagonal scheme described by Professor Luiz Carlos Pais. It was possible to highlight the outstanding performance of professors Jorge Nachreiner and Mucio Teixeira Júnior, who contributed to the objectification of knowledge to teach mathematics in educational institutions in Campo Grande, in the period considered, taking as a reference the major parameters in force in the country as well as the specifics of the context social and cultural in which they were inserted.